Medicolegal knowledge and its practice among physiotherapists in Maharashtra - Damle, Aditi R.; Dharmapuri, Venu M.; Dabadghav, Rachana P. (International Journal Of Community Medicine And Public Health, 2023)
Background: Physiotherapy is a modern science and an independent profession. Physiotherapists are expected to conduct professional practice according to the existing laws and follow the guidelines of the respective state councils. Awareness about patients’ rights is increasing, as are malpractice cases and as professionals who are in constant contact with their clients, physiotherapists need to safeguard themselves from a medicolegal perspective. Having appropriate knowledge of medicolegal aspects and practicing accordingly will protect them against legal damages while maintaining professional integrity. This study aimed to find the level of medicolegal knowledge and its practice among physiotherapists in Maharashtra. Methods: An observational, cross-sectional study was conducted in Maharashtra, India. A self-made, validated questionnaire was distributed online and 100 physiotherapists across Maharashtra, accessed via the convenience sampling method, were surveyed. The collected data was analysed using descriptive statistics. Results: The average knowledge was 50.38%, but the average correct practice was 71.86%. These findings showed that the physiotherapists were practicing according to basic knowledge and they needed to improve their knowledge of aspects such as the Maharashtra Act II of 2004, documentation, applicable laws and professional indemnity to practice with unquestionable protection against legal proceedings. Conclusions: Physiotherapists in Maharashtra have basic knowledge of the governing body and of the legal aspects of their profession. With medical negligence cases on the rise, they need to update themselves about the details to conduct a safe and efficient practice. This will enhance their professional competence and provide legal and financial security.